Characteristic Analysis of Featured Genes Associated With Stemness Indices in Colorectal Cancer - Lu, Yongqu; Zhou, Xin; Liu, Zhenzhen; Wang, Wendong; Li, Fei; Fu, Wei (Frontiers in Molecular Biosciences, 2020)
Cancer stem cells (CSCs) with self-renewal play an important role in tumor initiation and progression and are associated with drug resistance in cancer therapy. Here, we investigated the characteristics of stem cell-related genes in colorectal cancer (CRC) based on datasets from The Cancer Genome Atlas (TCGA) and Oncomine. We found that the stemness indices were significantly overexpressed in CRC tissues and were associated with patient survival. Weighted gene co-expression network analysis (WGCNA) was performed to determine the modules of stemness and featured genes. Significant modules and 8 genes (BUB1, BUB1B, CHEK1, DNA2, KIF23, MCM10, PLK4 and TTK) were selected according to the inclusion criteria. Expression analyses of transcription and protein levels confirmed internal correlation and their relevance with the tumor. Functional analysis of these genes demonstrated their enrichment in pathways, including checkpoint, chromosomal region and protein serine/threonine kinase activity. These results suggested that the characteristics of the featured genes fit well with CRC pathology and could provide new strategies for individual prevention and treatment.